2018
DOI: 10.1002/chem.201705267
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiazole‐Based Cycloplatinated Chromophores: Synthetic, Optical, and Biological Studies

Abstract: Cycloplatinated complexes based on 2-(4-substituted)benzothiazole ligands of type [Pt(R-PBT-κC,N)Cl(L)] (PBT=2-phenylbenzothiazole; R=Br (1), Me N (2); L=dimethyl sulfoxide (DMSO; a), 1,3,5- triaza-7-phosphaadamantane (PTA; b), triphenylphosphine 3,3',3''-trisulfonate (TPPTS; c)) and [Pt(Br-PBT-κC)Cl(PTA) ] (3) are presented. On the basis of the photophysical data and time-dependent (TD)-DFT calculations (1 a and 2 a), the low-lying transitions (absorption and emission) were associated with ligand-center (LC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 151 publications
5
53
0
Order By: Relevance
“…However, in the thienylpyridine derivative 1 f , it is the sulfur atom instead of the H−C proton of the thiazoline ring that is oriented toward the Pt center. The Pt⋅⋅⋅S distance (3.15 Å) is shorter than the van der Waals limit (3.55 Å) and comparable to those reported in trans ‐[Pt(Br‐pbt‐κC)Cl(PTA) 2 ] (3.073 Å; PTA=1,3,5‐ triaza‐7‐phosphaadamantane) or in the penta‐coordinated cation [Pt(ppy)(9S3)] + [2.9518(17) Å, 9S3=1,4,7‐trithiacyclononane] . In the crystals, a certain degree of π stacking involving the bzq and oxd ligands was observed for 1 a , whereas only offset secondary interactions were found in 1 d and 1 f (Figures S5–S7, Supporting Information).…”
Section: Resultssupporting
confidence: 72%
“…However, in the thienylpyridine derivative 1 f , it is the sulfur atom instead of the H−C proton of the thiazoline ring that is oriented toward the Pt center. The Pt⋅⋅⋅S distance (3.15 Å) is shorter than the van der Waals limit (3.55 Å) and comparable to those reported in trans ‐[Pt(Br‐pbt‐κC)Cl(PTA) 2 ] (3.073 Å; PTA=1,3,5‐ triaza‐7‐phosphaadamantane) or in the penta‐coordinated cation [Pt(ppy)(9S3)] + [2.9518(17) Å, 9S3=1,4,7‐trithiacyclononane] . In the crystals, a certain degree of π stacking involving the bzq and oxd ligands was observed for 1 a , whereas only offset secondary interactions were found in 1 d and 1 f (Figures S5–S7, Supporting Information).…”
Section: Resultssupporting
confidence: 72%
“…Only platinum derivative has emerged as an effective inductor of apoptotic death on HepG2 and MCF-7 cells and caused cell cycle arrest at G0/G1 phase while palladium was inactive. On the other hand, the inclusion of 2-(4-substituted)benzothiazoles (compound 18 in Figure 5) as ligands resulted in potent cytotoxic agents through tubulin polymerization in A549 and HeLa cell lines [51].…”
Section: Thiazole and Metal Complexesmentioning
confidence: 99%
“…Besides, ease thermal access to non‐emissive metal centered d‐d excited states and also direct solvent interactions should not be ruled out. [17a], …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, cycloplatinated(II) complexes have also attracted growing attention for their possible use as anticancer drugs and the results are quite promising . These complexes, possess strong σ(Pt–C) bonds what increases their stability in physiological conditions, avoiding off‐target reactions, and, therefore, simplifies the potential therapeutic applications . Additionally, recent studies have also demonstrated that the antiproliferative properties of some of these platinum complexes improved upon attaching a second Au I unit to the organometallic Pt compound .…”
Section: Introductionmentioning
confidence: 99%